1957
DOI: 10.1085/jgp.40.6.833
|View full text |Cite
|
Sign up to set email alerts
|

The Chemistry of Insect Hemolymph

Abstract: A curious feature of insect blood, shown by many analyses, is the apparent absence of all but minute amounts of sugar (for reviews, see Beutler, 1939;Babers, 1941;Buck, 1953). Reducing substances are abundant, but (except in the case of a few species) the greater part of these are not fermentable by yeast and are therefore presumably not sugar. Typical are data on the silkworm, Bombyx mori, in which the reported levels of blood sugar range from zero up to about 30 rag. per 100 ml. (Florkin, 1937;Kuwana, 1937; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
1

Year Published

1966
1966
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 323 publications
(77 citation statements)
references
References 14 publications
(8 reference statements)
4
68
1
Order By: Relevance
“…However, as depicted in Table 1, the major insect blood sugar trehalose (Wyatt and Kale, 1957) has a certain potential to compete with sucrose for transport, indicating that this disaccharide might also be a substrate for SCRT, yet with a reduced potency. The Drosophila SCRT resembles sucrose transporters in plants, including a crucial region that is considered to be a sucrose transporter signature.…”
Section: Discussionmentioning
confidence: 99%
“…However, as depicted in Table 1, the major insect blood sugar trehalose (Wyatt and Kale, 1957) has a certain potential to compete with sucrose for transport, indicating that this disaccharide might also be a substrate for SCRT, yet with a reduced potency. The Drosophila SCRT resembles sucrose transporters in plants, including a crucial region that is considered to be a sucrose transporter signature.…”
Section: Discussionmentioning
confidence: 99%
“…Since 1956 it was known that trehalose is a very abundant component of insect hemolymph [39], and also since then, various reports have shown that trehalose levels can vary greatly [36,39]. As stated before, there are several reasons for this: Trehalose levels respond to a variety of environmental conditions including changes in ambient and concomitant bodily temperature, nutritional status, developmental stage, oxidative stress, salinity, etc., such that the term 'enantiostasis' was coined to describe this condition.…”
Section: Hemolymph Trehalose Concentrations: Enantiostasismentioning
confidence: 98%
“…Adult Lepidoptera maintain low haemolymph [Na + ], in some cases low enough to reverse the muscle Na + gradient (Fitzgerald et al, 1996). To maintain haemolymph osmotic balance in the absence of Na + , Lepidoptera maintain high haemolymph concentrations of carbohydrates (Wyatt and Kalf, 1957;Wyatt, 1961), and, as a group, maintain muscle excitability to lower temperatures than members of Diptera and Hymenoptera, which have more 'conventional' (high) extracellular [Na + ] (Natochin and Parnova, 1987;Goller and Esch, 1990). Although we observed low cation concentrations in more cold-tolerant flies, we observed no differences in haemolymph osmolality between warm-and cold-acclimated D. melanogaster, nor among Drosophila species.…”
Section: Cold-tolerant Flies Maintain Low Haemolymph Cation Concentramentioning
confidence: 99%